Social care facility management in Malaysia: A case of Hospital Permai Tampoi, Johor Bahru - Wan Samsuddin, Wan Roslina; Omar, Abdul Jalil (American Scientific Publishers, 2018)
Social Care Facility Management (SCFM) is an important element in ensuring the management practices used meet the standards set by the Malaysian Ministry of Health. In the context of Facility Management (FM) for social real estate it is recognised as Social Care Facility Management (SCFM) that managed premises for clients who require social care, such as children, the elderly, and people with disabilities, including mental patients. Malaysia has two mental patients institutions known as Hospital Bahagia Ulu Kinta, Perak and Hospital Permai Tampoi, Johor. Both hospitals are subject to Care Centres Act 1993. However, there are still many weaknesses appear in the management of these mental patient institutions in Malaysia. Outcome of this study shows that this research focused on management practices and SCFM approaches being implemented in Mental Patient Institutions exclusively or otherwise.